An influence of a modulating signal starting phase on the modulation detection - SĘK, A. P.; SKRODZKA, E. B. (Archives of Acoustics, 1999)
This paper is concerned with an influence of a modulator starting phase on psychometric functions of amplitude modulation (AM) and frequency modulation (FM) detection, for low modulation rates, i.e. fmod = 2 and 5 Hz. For a sinusoidal carrier at a frequency of 0.25, 1 and 6 kHz it is shown that there is no effect of a sinusoidal modulator starting phase. Data shown in this paper are consistent with predictions of models based on excitation pattern changes and with a concept according to which AM/FM detection at low modulation rates depends mainly on maximum and minimum values of signal amplitude/frequency. Time intervals between beginning of a signal and the moment when the signal reaches maximum/minimum value of amplitude/frequency and a pattern of physical parameter changes as a function of time seem to be less crucial when the changes are continuos in time.